Religions in contemporary Africa : an introduction - Grillo, Laura S., 1956-; Van Klinken, A. S.; Ndzovu, Hassan J. (London: New York: Routledge, 2019)
Religions in Contemporary Africa is an accessible and comprehensive introduction to the three main religious traditions on the African continent, African indigenous religions, Christianity and Islam. The book provides a historical overview of these important traditions and focuses on the roles they play in African societies today. It includes social, cultural and political case studies from across the continent on the following topical issues: - Witchcraft and modernity - Power and politics - Conflict and peace - Media and popular culture - Development - Human rights - Illness and health - Gender and sexuality With suggestions for further reading, discussion questions, illustrations and a list of glossary terms this is the ideal textbook for students in religion, African studies and adjacent fields approaching this subject area for the first time.
Introduction: Why and how this book helps you understand religions in Africa -- Major religions in Africa -- African indigenous religions -- Christianity in Africa -- Islam in Africa -- Neo-traditional religious movements in Africa -- Pentecostal-charismatic movements in Africa -- Islamic reform movements in Africa -- Topical issues of religions in Africa -- Religion, witchcraft and modernity in Africa -- Religion, power and politics in Africa -- Religion, conflict and peace in Africa -- Religion and development in Africa -- Religion and human rights in Africa -- Religion, illness and health in Africa -- Religion and gender in Africa -- Religion and sexuality in Africa -- Religion, media and popular culture in Africa.
Includes bibliographical references and index.
Keywords: Africa -- Religion